Burden of near vision loss in China: findings from the Global Burden of Disease Study 2019. Issue 3 (16th October 2021) - Jin, Guangming; Zou, Minjie; Liu, Chi; Chen, Aiming; Sun, Yi; Young, Charlotte Aimee; Li, Yi; Zheng, Danying; Congdon, Nathan; Han, Xiaotong
Abstract : Purpose: To investigate the burden of near vision loss (NVL) in China by year, age and gender from 1990 to 2019. Methods: We used estimates from the Global Burden of Disease (GBD) 2019 study to report the prevalence and disability-adjusted life-years (DALYs) due to NVL in China. Estimates of crude counts and age-standardised rates per 100 000 population are accompanied by 95% uncertainty intervals (UIs). We summarised the age-specific and sex-specific patterns and trends regarding the burden of NVL in China, compared with seven neighbouring countries. Results: From 1990 to 2019, the all-age number and rate for NVL prevalence and DALYs increased significantly in China (all p<0.001). The age-standardised rate decreased from 7538.1 (95% UI 6946.3 to 8075.1) to 7392.9 (95% UI 6855.8 to 7890.5) per 100 000 population for NVL prevalence (p=0.107), and from 74.9 (95% UI 69.6 to 79.9) to 73.8 (95% UI 70.6 to 80.1) per 100 000 population for DALYs (p=0.388). Women had higher NVL prevalence (t=170.1, p<0.001) and DALYs (t=192.5, p<0.001) than men. Higher disease burden of NVL was observed in the middle-aged and elderly population. The age-standardised prevalence and DALY rate attributable to NVL in China were lower than in India, North Korea, Pakistan (all p<0.001), but higher than Russia, South Korea, Singapore and Japan (all p<0.001). Conclusions: Despite a small decrease in age-standardised prevalence and DALYs due to NVL in China in the past two decades, the existing burden is still considerable and significantly higher compared with neighbouring developed countries. An approach that includes all stakeholders is needed to further reduce this burden.